Systematic Literature Review : Dampak Tax Incentives terhadap Inovasi dan Pertumbuhan Ekonomi - Lady Karlinah; Liem Yan Sugondo; Mira Falatifah; Daniel Artha Wahyuda (Owner : Riset dan Jurnal Akuntansi, 2025)
This study systematically reviews the impact of tax incentives on innovation and economic growth. Tax incentives, as a fiscal policy tool, have the potential to stimulate investment in research and development (R&D), fostering innovation in key sectors such as technology and manufacturing. The findings suggest that tax incentives can accelerate innovation and long-term economic growth, particularly in countries with economic stability and a private sector ready to innovate. However, the effectiveness of this policy depends on factors such as policy design, macroeconomic conditions, and supporting regulatory and socio-political factors. This study concludes that to maximize the impact of tax incentives, policies should be tailored to specific sectoral needs and supported by other holistic policies.